Financial institutions development and its influence on green finance: Does research and development matters? - Lee, Li Ying; Ng, Ming Wen; Phua, Tang Ning; Wong, Xun Yi (2024)
This study looks into how China's green finance is affected by the growth of financial institutions and research and development (R&D). Within the framework of China's economy, the study aims to comprehend the relationship between the independent factors, financial institution development and R&D, and the dependent variable, green financing. The 24 observations that make up the annual data from 1998 to 2021 are used in this study. In order to investigate the long-term relationships and the significance of these factors in influencing green finance, this study uses advanced econometric techniques, such as the Unit Root Test, ARDL Cointegration Bounds Test, and robustness estimations through Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS). The ARDL Cointegration Bounds Test is used to find long-term equilibrium relationships between the variables after the Unit Root Test, which is used to determine whether the time series data is stationar. As supplementary estimations, FMOLS and DOLS are employed to guarantee the validity of the results. The main conclusions of the study are outlined, together with their implications for the growth of green finance in China.